The impact of dental appearance on young adults’ daily life. A pilot study - Loukasmäki, Elli (My University, 2026)
Objective: To investigate perceptions of aesthetically acceptable dental appearance and associated factors, to assess self-rated dental appearance and its psychosocial impact, and to explore whether there is a cutoff value between self-rated and acceptable dental appearance beyond which the perceived disadvantage increases. Materials and methods: An electronic cross-sectional study was conducted among students at the University of Turku. Respondents (n = 45) rated their own dental appearance and defined their threshold for aesthetically acceptable dentition using the Aesthetic Component of the Index of Orthodontic Treatment Need (AC/IOTN). Psychosocial impact was assessed using the Finnish versions of the Orofacial Esthetic Scale (OES-Fi) and the Psychosocial Impact of Dental Aesthetics Questionnaire (PIDAQ-Fi). Symptoms of anxiety and depression were evaluated using the Generalized Anxiety Disorder-7 (GAD-7) and the Patient Health Questionnaire-9 (PHQ- 9). Results: No statistically significant associations were found between orthodontic treatment history, anxiety or depression symptoms and perceptions of aesthetically acceptable dental appearance. Self-rated dental appearance was statistically significantly associated with all PIDAQ domains, whereas no significant associations were observed for the PIDAQ or OES sum scores. Of respondents, 64% rated their own dentition close to their self-defined acceptable threshold. No clear threshold effect was identified beyond which the discrepancy between acceptable and self-rated appearance consistently predicted greater disadvantage, except in the Dental Self-Confidence domain. Conclusions: Psychosocial impact appears to be more closely linked to individuals' own perceptions of dental appearance than to background or contextual factors. These findings emphasize the importance of patient-reported outcomes alongside clinical assessments of dental aesthetics.

Tällä pilottitutkimuksella oli kolme tavoitetta: 1) selvittää nuorten aikuisten näkemyksiä esteettisesti hyväksyttävästä hampaistosta ja tekijöistä, jotka ovat yhteydessä tähän arvioon, 2) tarkastella, miten tutkittavat arvioivat oman hampaistonsa ulkonäköä ja sen psykososiaalisia vaikutuksia sekä 3) analysoida, voidaanko ulkonäöltään hyväksyttävän ja oman hampaiston ulkonäön erotukselle määrittää kynnysarvo, jonka ylittyessä oman hampaiston ulkonäön vaikutus jokapäiväiseen elämään on epäedullinen. Aineisto koostui Turun yliopiston opiskelijoista (n = 45), jotka vastasivat sähköiseen REDCapkyselyyn. Hampaiston ulkonäköä arvioitiin käyttäen englantilaisen Index of Orthodontic Treatment Need (IOTN) -työkalun hampaiston ulkonäköä arvioivaa AC/IOTN-osiota. Hampaiston ulkonäön psykososiaalisia vaikutuksia mitattiin orofakiaalisen estetiikan (OES-Fi) ja psykososiaalisen vaikutuksen (PIDAQ-Fi) kyselyillä sekä vastaajan kokemia ahdistus- ja masennusoireita yleisesti käytetyillä GAD-7- ja PHQ-9-kyselyillä. Tuloksia analysoitiin käyttäen kumulatiivista logistista regressioanalyysiä. Vastaajan oikomishoitohistorialla tai koetuilla ahdistus- ja/tai masennusoireilla ei havaittu yhteyttä siihen, millaista hampaistoa hän piti esteettisesti hyväksyttävänä. Arviolla oman hampaiston ulkonäöstä oli tilastollisesti merkitsevä yhteys kaikkiin psykososiaalisen vaikutuksen mittarin (PIDAQ-Fi) osa-alueisiin. Hyväksyttävän ja oman hampaiston ulkonäön ACasteikkoa käyttäen määritellylle erotukselle ei havaittu selkeää kynnysarvoa, jonka ylittyessä oman hampaiston ulkonäkö haittaisi arjen eri tilanteissa, kotona, työssä tai vapaa-aikana. Tulokset korostavat yksilön oman mielipiteen huomioimista arvioitaessa hampaiston ulkonäköä.
Keywords: Dental aesthetics; Psychosocial impact; Orthodontics